Contemporary Turkish - Russian Relations from Past to Future - Topsakal, Ilyas; Askerov, Ali; Co-Editors: Nafikov, Ilsur and Atalay, Samet (Istanbul University Press, 2021)
The historical experience of relations between Turkey and Russia has gone through different stages. The first attempts at diplomatic relations, which date back to the 15th century, have developed over time and have begun to determine the geopolitical balance of power in the region. At the same time, certain regions have gained importance in the context of Russia and Turkey relations (a context in which strategic interests have been an area of constant search for compromise solutions): Central Asia, the Balkan Peninsula, the Caucasus region and the Middle East. Along with this, the historical roots of Turkey lie in the Eurasian region among the Turkic peoples of Russia, and the confessional values of Orthodox culture originated in the Byzantine Empire. From this point of view, Russian-Turkish relations can be seen as are an intertwinement of a large number of sensitive issues and difficult compromise solutions. The regional mutual influence of Russia and Turkey seems to be a long process that developed during the period of the Ottoman and Russian Empires. At the stage of the formation of the Moscow state, Ivan the Third understood the importance of the participation of Russian merchants in the markets of Istanbul and sent a letter to the Ottoman Sultan Bayezid the Second on August 31, 1492, asking for free movement and trade. Having received a positive answer, Ivan the Third decided to send his ambassador to the Ottoman court in 1495, and thus diplomatic relations between İstanbul and Moscow began. Subsequently, the strengthening of the Russian Empire and its active participation in European politics led to a direct clash between the Ottoman Empire and Russia. Until the conflict of interest during the first World War, Russia and Turkey experienced the difficulties of a large multinational poly-confessional state in different ways, overflowing with ideas of constitutional reforms and democratic transformations. Following the end of First World War, the collapse of the Ottoman Empire and the change of state formation, i.e. the republic, once again pushed Soviet government and Turkey into a dialogue and consolidation efforts in the region: the Turkish War of Independence under the leadership of Mustafa Kemal Ataturk and the straits questions, diplomatic friction with the West at the Lausanne Conference and the support of diplomats from Ankara by the Soviet delegation. The 20th century largely predetermined the foreign policy orientation of the Republic of Turkey. In 1952, Turkey and Greece became members of the North Atlantic Treaty Organization at the NATO Summit in Lisbon. As a result of the confrontation between NATO and the Warsaw Pact, Turkey and Russia been forced to build relations through the prism of the foreign policy agendas for a long time. The end of the 20th century and especially the beginning of the 21st century brought Russia to the level of the state and it began to build its foreign policy strategy based on national interest. As a result of V. V. Putin's speech at the Munich conference on February 10, 2007, he set the task of creating a "multipolar world" as an objective. At the same time, Turkey continued to be an active participant in European politics, counting on fully-fledged integration into the European Union, but did not receive a specific answer and was forced to postpone the decision. In this regard, Turkey at a certain point made an independent decision to refuse to participate in the process of European integration and to develop its independent foreign policy strategy in the region. The catalyst for this decision was an unsuccessful coup attempt on July 15, 2016. Regional and global challenges caused by the Syrian crisis and confrontation of the international coalition in the Middle East have posed new challenges to Russian-Turkish relations. The attempts to consolidate the opinions and visions of specialists in various spheres of relations between Russia and Turkey relations have led the authors to highlight these aspects in regional interactions of various countries.